Pelatihan Laporan Keuangan dan Sumber Daya Manusia Untuk Peningkatan Ekonomi Kreatif pada Agrowisata Desa Kalisapu, Kabupaten Slawi - Imang Dapit Pamungkas; Ngurah Pandji Mertha Agung Durya (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
Kalisapu Village, Slawi Regency, has significant agrotourism potential to be developed as part of the local creative economy. However, the utilization of these natural resources has not been balanced with adequate human resource (HR) capacity. This article discusses HR training conducted to improve the ability of local communities to manage agrotourism with a creative economy approach. Training methods include workshops, mentoring, and evaluations designed to empower communities in managing innovative and sustainable agrotourism businesses. The results of the training showed a significant increase in community understanding and skills related to creative business management, digital marketing, and financial management. This article also identifies the challenges and opportunities faced in developing a creative economy in the village agrotourism sector.